Simulate and Analyze the Effect of the Magnetic System on the Electron Oscillatory Motion and the Formation of the Free Electron Laser Beam - Jaafar Hussein Sabri; Thair AbdulKhalil Al-Aish (Ibn Al-Haitham Journal for Pure and Applied Sciences)
The free electron laser (FEL) represents a significant advance over conventional laser systems by allowing a wide range of operating wavelengths without changing the active laser medium or undergoing extensive redesign. Central to this ability is the Wiggler component, which influences many of the properties of the emitting laser through its wavelength ( ) This study investigates the influence of ( ) on the FEL's performance metrics, including magnetic field strength, photon wavelength, and laser power, by utilizing MATLAB R2023a for simulation. The study employs a set of equations to explore how variations in ( ) affect these parameters. The undulator's role, a critical component of the FEL, is analyzed for its ability to convert high-speed electron kinetic energy into coherent light by manipulating electron trajectories through Lorentz force interactions. Results indicate a direct proportionality between ( ) and both the generated magnetic field and output photon wavelengths, suggesting that ( ) is a pivotal factor in optimizing FEL performance. The findings highlight potential enhancements in laser power and stability that could benefit a range of applications, from medical to military. This paper not only reaffirms the critical role of ( ) in the operational efficiency of FEL systems but also guides future design strategies for advanced laser technologies.